Estratégias de narração do si: figurações da memória em Black Boy (American Hunger), de Richard Wright - Hermes, Ernani Silverio (2023)
This master thesis, inscribed in the field of Literary Theory, has as its central problem the following question: how the subject turns one's life story, one's world experience, into literary fabric? This problem is articulated in the horizon of North-American Literature, in a more specific way, of African-American Literature, since I chose as study object the autobiographical narrative Black Boy (American Hunger): a record of childhood and youth (2005 [1945/1977]), by the writer Richard Wright (1908-1960). The hypothesis I raise is that, having memory figurations as its center, a range of strategies is used in order to construct the narrative of the self. This situation is put to proof through the literary analysis rooted in Narrative Theories and Cultural Studies. The critical exercise accomplished in this theoretical bias is backed by the tripod narrative, memory, and identity, concepts articulated according to Gérard Genette (1995), Mieke Bal (2021), Roland Barthes (1973; 2004), Walter Benjamin (2012), Paul Ricoeur (2010; 2007), Chimamanda Ngozi Adichie (2009), Maurice Halbwachs (2003), Jöel Candau (2016), Birgit Neumann (2008), Jan Assmann (1995), Astrid Erll (2008), Frantz Fanon (2008), Dennys Cuche (1999), W. E. B. Du Bois (2007) and Kathryn Woodward (2014), among other voices called to the text as long as the interpretative dynamics demands. Thereby, in the two theoretical chapters, I retake a discussion about the three analytical categories cited, and, from Literary History articulated to the discussions on African-American identity, to discuss definitions for African-American identity and African-American Literature, as well as its historical course. Regarding the analytical chapters, in the first one, I observe the strategies of narration of the self that are centered on the construction of an individual narrative, observing the utterance of a self-referential discourse, the representation of memory, and the perception of identity dynamics. In the next one, I ascertain the entanglement (SCHAPP, 2007) of the self, which means, the management of narratives effectuated in Wright’s narrative project from vectors related to the dialogue with a narrative capital linked to the geographical context that traverses the writing subject, to History, and this narrative range as a way of cultural memory construction and reassessment of nation comprehension. Therefore, the development of strategies of narration of the self is confirmed in two macrostructures: in the first one, the narrated self, which aims to reconstruct his subjectivity narrative through memory, getting closer to his past experience and his perceptions about identity; in the second one, the entangled self, the management of a narrative capital that crosses the subject subjective fabrics and promotes a transit from individual sphere to the collective, in which the life story of the individual being is reexamined and the relation to the nation is resized.